An empirical analysis of energy intensity and the role of policy instruments. (October 2020) - Azhgaliyeva, Dina; Liu, Yang; Liddle, Brantley
Abstract: The reduction of energy intensity is important for sustainable economic growth, especially in non-OECD countries where energy demand growth is high. Understanding the impact of policies on energy intensity can help policy-makers to reduce energy intensity. Using empirical methods and cross-country data from 44 countries over the period 1990–2016, we study the determinants of energy intensity. The common correlated effects mean group estimator is employed since it addresses nonstationarity, cross-sectional dependence, and heterogeneity—all three of which exist in the data. Both GDP per capita and economy-wide energy prices are shown to be negatively associated with energy intensity. The empirical results provide evidence that several policy instruments are effective in reducing energy intensity: (i) standards, and labeling; (ii) government direct investment; (iii) strategic planning and support; (iv) fiscal measures/taxes; and (v) grants and subsidies. The duration of the policy is more important than the mere existence of the policy in demonstrating the policy's effectiveness. Highlights: Higher GDP per capita and energy prices lead to lower energy intensity. Five types of energy efficiency policies are shown to lower energy intensity. Among the policies are: standards, government direct investment, taxes, and grants. The duration of the policy is more important than the mere existence of the policy.